A novel test method for mechanical properties of characteristic zones of girth welds. (1st December 2021) - Nie, Hailiang; Ma, Weifeng; Xue, Kai; Ren, Junjie; Dang, Wei; Wang, Ke; Cao, Jun; Yao, Tian; Liang, Xiaobin
Abstract: The safety evaluation of girth welds is an important issue for steel pipes. Current standards and studies all regard the weld as a uniform material, ignoring its inhomogeneity. In this paper, a specimen processing method for weld characteristic zones is proposed. Based on the natural morphology of the weld structure, specimens are accurately designed and processed for each characteristic zone. In addition, a testing method to determine the tensile properties in the characteristic zones of the weld is also proposed, solving the absence of weld mechanical properties in existing steel pipe safety evaluations. This method was used to test an X80 automatic girth weld, and the results showed that the tensile properties significantly differed between different characteristic zones of the girth weld. The inhomogeneity displayed in this weld demonstrates how a more detailed assessment of weld properties should be considered in practical engineering and safety evaluations. Highlights: An innovative testing method for tensile property nonuniformity of weld material. Design and machining method of micro-tensile specimen of weld material. A foundation for improving the accuracy of pipeline safety assessment.